Density, Shatter Index and Heating Value of Briquettes Produced from the Leaves of Terminalia Mentalis and Sawdust of Daniela Oliveri - Oriabure, Ekhuemelo David; Terzungwue, Tembe Emmanuel; Emoh, Obute Faith (International Journal of Pure Agricultural Advances, 2017)
This study investigated some qualities of briquettes produced from the leaves of Terminalia mentalis and sawdust of Daniela oliveri as alternative to the conventional fuelwood resources used for domestic cooking. The leaves of Terminalia mentalis and sawdust of Daniela oliveri was collected and sundried to equilibrium moisture content. The samples were sieved into uniform fractions and used to produce briquettes at 25% of starch to sample as binder. The experimental design was a 2 x 3 factorial in Completely Randomised Design (CRD). Densities, Shatter index and Combustion related properties such as % moisture content, % volatile matter, % fixed carbon, % ash content and Specific heat of combustion (Heating value) were investigated from the produced briquettes. Terminalia mentalis briquettes recorded a highly significant relaxed density of 0.668 g/cm3 in seven (7) days. Terminalia mentalis briquettes recorded a higher weight loss of 2.00% and lower shatter resistance of 98% which was significantly lower than Terminalia mentalis + Daniela oliveri briquettes with weight loss of 0.02% and higher shatter resistance of 99.98%. The specific heat of combustion value ranged from 9704.0 kcal/kg to 11053.0 kcal/kg for Terminalia mentalis and Terminalia mentalis + Daniela oliveri respectively. The percentage Ash content was significant, for Terminalia mentalis briquettes which recorded a higher %Ash content of 12.56% , 30.93% fixed carbon and 56.52% volatile matter while there was no significant difference in %moisture content. The effect of particle size also showed that there was no significant difference in % Volatile matter and heating value. The relatively high heating values of the briquettes indicate that the materials can be a very good alternative source of energy for cooking.